The Effect of Zoning on Learning Potential in the Education Era - Sashi Kirana H; Fegy Regita Cahyani Ibrahim; Siti Nur Amalia Antaza; A. Octamaya Tenri Awaru (Formosa Journal of Applied Sciences, 2023)
The problem in education in Indonesia is about equal distribution of student outcomes, so a Zoning system is implemented. When this system was implemented, teachers had to face adaptation to the new system, learning methods in schools were changed because of the mix of students who had differences in academic terms. The author's aim in creating this journal is to see the development of equality and new learning methods that are applied to each student. The research method used is processing data by examining various data sources such as magazines, books and other relevant documents. This research concludes that: 1). The zoning system has many pros and cons. 2). Improving the quality of public school education. 3). affect students' psychosocial skills. 4). It is a challenge for teachers to create learning methods for students who have differences in academic understanding.